Nickel-Lanthanum Impregnated into Natural Zeolite as a Catalyst for Biofuel Production from Sunflower Oil via Hydrocracking Process - Erik Budi Santiko; Sarah Fauziah; Sugeng Priyanto; Yustinah Yustinah; Lenny Marlinda; Sudibyo Sudibyo; Abdul Aziz; Peri Oktiarmi; Indri Yati; Muhammad Al Muttaqii (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
The increasing demand for crude oil or fossil fuel as a raw material for oil fuel has been steadily rising over time in line with the development that is taking place in Indonesia. However, biofuels are potential vegetable fuels that can be developed as alternative energy because they are renewable and can be renewed to overcome the energy crisis in the future. For this purpose, a double metal catalyst (impregnated with nickel and lanthanum), is used to make biofuels from sunflower seed oil. The effect of metal ratio on the yield of biofuel products is the concern in this study. The temperature of hydrocracking process was 250-330 ℃ with ratio of metal 5% and 10% (metal ratio 1:1 and 1:2). X-ray diffraction (XRD) shows that natural zeolite has a clinoptilolite phase, X-Ray Fluorescence (XRF) shows that acid and base activation increases the Si/Al ratio from 4.5 to 5, Scanning Electron Microscope – Energy Dispersive X-Ray (SEM-EDX) shows images of natural zeolite surfaces in the form of aggregate pieces, and Brunauer Emmett Teller (BET) shows that acid and base activation increases SBET from 29.96 to 49.73 m2/g and forms a hierarchical natural zeolite. The impregnation of Ni-La/Zeolite catalyst has been successfully carried out using the incipient wetness impregnation method and the best catalyst results were obtained, namely Ni-La/Zeolite 10% (1:2) with a surface area of 15.33 m2/gS. The addition of Nickel and Lanthanum metals caused a decrease in the surface area and average pore diameter of the zeolite. The lowest surface area and average pore diameter were found in the variation of the Ni-La/Zeolite 10% (1:2) catalyst, namely 15.33 m2/g and 13.99 nm. The highest hydrocarbon yield was found in the hydrocracking process with the Ni-La/Zeolite 10% (1:1) catalyst with gasoline, kerosene and gasoil fractions of 0.91; 0.39 and 8.32 (%wt), respectively. The hydrocarbon compound composition of the catalyst includes n-paraffin 4.43%, isoparaffin 0.21%, cycloparaffin 2.99% and olefin 2.71%. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).